2017
DOI: 10.1186/s12885-017-3071-5
|View full text |Cite
|
Sign up to set email alerts
|

BK-UM in patients with recurrent ovarian cancer or peritoneal cancer: a first-in-human phase-I study

Abstract: BackgroundBK-UM (CRM197) is a mutant form of diphtheria toxin and a specific inhibitor of heparin-binding epidermal growth factor-like growth factor (HB-EGF). We assessed the safety, pharmacokinetics, recommended dose, and efficacy of BK-UM in patients with recurrent ovarian cancer (OC) or peritoneal cancer (PC), and measured HB-EGF levels in serum and abdominal fluid after BK-UM administration.MethodsEleven patients with advanced or recurrent OC or PC were enrolled and treated with BK-UM via the intraperitone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…HB-EGF-targeted agents have been tested in two phase I clinical trials, which investigated the safety, tolerability, and efficacy of the inhibitory monoclonal antibody to HB- EGF KHK2866 in patients with advanced ovarian cancer and of BK-UM in patients with recurrent ovarian cancer (21,23). Companion diagnostics for each agent were also developed (8,24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HB-EGF-targeted agents have been tested in two phase I clinical trials, which investigated the safety, tolerability, and efficacy of the inhibitory monoclonal antibody to HB- EGF KHK2866 in patients with advanced ovarian cancer and of BK-UM in patients with recurrent ovarian cancer (21,23). Companion diagnostics for each agent were also developed (8,24).…”
Section: Discussionmentioning
confidence: 99%
“…Companion diagnostics for each agent were also developed (8,24). The studies found that serum HB-EGF levels were reduced by intravenous injection of KHK2866 (23), and significantly reduced by intraperitoneal administration of BK-UM in patients with high levels of serum HB-EGF (>125 pg/ml by ELISA) (21). However, the KHK2866 antibody caused reversible neuropsychiatric toxicity and its development has been discontinued (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the blockage of HB-EGF can inhibit both HB-EGF-dependent homodimerization and heterodimerization, demonstrating that an inhibitor of HB-EGF suppresses AKT signaling as well as ERK. CRM197, an inhibitor of HB-EGF, and an anticancer agent with a high molecular weight, was shown to be clinically safe and effective for patients with ovarian cancer (23). The combination of TKIs and CRM197 may be a potential treatment for patients with NSCLC with EGFR mutation.…”
Section: Discussionmentioning
confidence: 99%